2000
DOI: 10.1038/35001568
|View full text |Cite
|
Sign up to set email alerts
|

Producer–decomposer co-dependency influences biodiversity effects

Abstract: Producers, such as plants and algae, acquire nutrients from inorganic sources that are supplied primarily by decomposers whereas decomposers, mostly fungi and bacteria, acquire carbon from organic sources that are supplied primarily by producers. This producer-decomposer co-dependency is important in governing ecosystem processes, which implies that the impacts of declining biodiversity on ecosystem functioning should be strongly influenced by this process. Here we show, by simultaneously manipulating producer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
171
2
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(186 citation statements)
references
References 26 publications
6
171
2
7
Order By: Relevance
“…However, microbial diversity has rarely been studied in the context of productivity of microbial communities (Naeem et al, 2000;Langenheder et al, 2010;Peter et al, 2011). Similarly, the process of primary succession, where freshly formed habitats become colonized by a sequence of organisms, has a long-standing tradition of study in the ecology of macroscopic organisms, yet is only since recently emerging as a topic in microbial ecology (Fierer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, microbial diversity has rarely been studied in the context of productivity of microbial communities (Naeem et al, 2000;Langenheder et al, 2010;Peter et al, 2011). Similarly, the process of primary succession, where freshly formed habitats become colonized by a sequence of organisms, has a long-standing tradition of study in the ecology of macroscopic organisms, yet is only since recently emerging as a topic in microbial ecology (Fierer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the impacts of consumer diversity on ecosystem functioning is particularly important because extinction threats are often higher for animals than for plants (14,15). Recent experiments suggest that changes in biodiversity may affect ecosystem processes through trophic interactions among species (16)(17)(18)(19). Countervailing effects of autotroph diversity and heterotroph diversity were observed recently in some studies; addition of heterotrophs can remove the positive relationship between diversity and production found in autotroph-only treatments (16,20), and algal biomass was reduced by increasing grazer diversity in a seagrass system (21).…”
mentioning
confidence: 99%
“…However, diverse communities were more likely to contain temperature-tolerant species and therefore retained more species than depauperate ones (Petchey et al, 1999). Further, the simultaneous manipulation of two trophic levels showed that neither algal nor bacterial species richness alone could explain the significant differences among microcosms, but that the algal biomass was a joint function of both algal and bacterial diversity implying important interactions among functional groups (Naeem et al, 2000). Studies on microbial communities are very useful as they can be carried out at very high species richness levels (Bell et al, 2005).…”
Section: Microbial Communitiesmentioning
confidence: 99%
“…Their study system consisted of semi-permanent rain pools from the base of European beech trees. In another approach, algal (producer) and bacterial (decomposer) species diversity were manipulated simultaneously, and algal biomass was measured as a proxy of primary production (Naeem et al, 2000). Algae were chosen randomly from a pool of eight, and bacteria were chosen from a pool of 12 species.…”
Section: Microbial Communitiesmentioning
confidence: 99%